2019
DOI: 10.1016/j.compositesa.2019.105565
|View full text |Cite
|
Sign up to set email alerts
|

Coupon scale Z-pinned IM7/8552 delamination tests under dynamic loading

Abstract: Dynamic impact onto laminated composite structures can lead to large-scale delamination. This can be mitigated by the introduction of through-thickness reinforcement, such as z-pins. Here, mode I & II and mixed-mode delamination tests have been designed and conducted at high loading rate, for both unpinned and Z-pinned coupons to study the effect of rate of loading. It was found that the Z-pins were not effective in delaying the dynamic crack initiation or resisting the dynamic propagation of delaminations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Rate dependence of the initiation stresses can thus be ignored. For IM7/8552, strain rate dependent 3-ENF Mode II tests revealed that the fracture energy is 0.97 N/mm [30] for high strain rate cases and 0.2 N/mm for Mode I fracture energy in high strain rate tests using DCB specimens [31]. Similar values are used in the current work.…”
Section: Continuum Modellingsupporting
confidence: 65%
“…Rate dependence of the initiation stresses can thus be ignored. For IM7/8552, strain rate dependent 3-ENF Mode II tests revealed that the fracture energy is 0.97 N/mm [30] for high strain rate cases and 0.2 N/mm for Mode I fracture energy in high strain rate tests using DCB specimens [31]. Similar values are used in the current work.…”
Section: Continuum Modellingsupporting
confidence: 65%
“…The results show that with increasing z-Pin content, the strength of quasi-isotropic laminates is reduced in a non-linear trend for both RTD and l environments, as shown in Figure 69. The mode I and II and mixed-mode delamination under high loading rate for both unpinned and Z-pinned coupons to study the effect of rate of loading was investigated by H. Cui et al [49,50] It was shown that the Z-pin effectiveness in dynamic tests is lower than that in quasi-static tests and the difference was more significant whenever mode I delamination prevails than that where mode II is the dominant case.…”
Section: Mal Responsementioning
confidence: 99%
“…The previous research has proven that z-pins can also increase the mode II delamination resistance of laminated composites effectively by forming a large-scale bridging zone. [18][19][20] Z-pins bridge the sliding crack and generate shear traction loads, which restrain the relative sliding of crack surface and thereby contribute to the improvement of mode II fracture toughness. Although the interlaminar properties were improved by introducing z-pins, the inplane fibers around z-pins are pushed aside obviously during z-pin insertion process.…”
Section: Introductionmentioning
confidence: 99%